2019
DOI: 10.1016/j.vaccine.2018.06.073
|View full text |Cite
|
Sign up to set email alerts
|

An environmental scan to examine stakeholder perspectives on human papillomavirus vaccination: A mixed methods study

Abstract: Results suggest the need for parent/adolescent education, specifically targeting key areas we identified: importance and benefits of HPV vaccine, and education and skill building in vaccine communication for HCPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…This indicates an important area for improvement because recent research shows engaging in these high quality recommendation practices significantly increases vaccination rates. 16 Consistent with previous research, 13,14,24,25 education for parents/adolescents and providers was often mentioned by our participants as a necessary step to increase vaccination rates among adolescents. Physicians believed that it would be important to provide education for adolescents by the school system during health and wellness classes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This indicates an important area for improvement because recent research shows engaging in these high quality recommendation practices significantly increases vaccination rates. 16 Consistent with previous research, 13,14,24,25 education for parents/adolescents and providers was often mentioned by our participants as a necessary step to increase vaccination rates among adolescents. Physicians believed that it would be important to provide education for adolescents by the school system during health and wellness classes.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, another study by our team focused on key Florida stakeholders (physicians, nurses, DOH professionals, and parents) found that stakeholders believe there is a perception among health care providers that HPV vaccination is less important because it is not a mandatory vaccine for school entry. 13 Additional research has found parent and physician support for mandatory vaccination. [34][35][36] Our quantitative results indicate that physicians who did not limit the number of vaccines administered during the visit were more likely to recommend HPV vaccine strongly and consistently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This includes both clinic-level factors, such as the ability of the clinic to stock the vaccine, the presence of tools like provider prompts and reminder-recall systems and peer influences as well as the characteristics of the broader community in which the provider practices . HCP peers may influence provider attitudes about vaccines or recommendation practices (P. W. Lake et al, 2019a , 2019b ). Providers who were characterized as “Ambivalent HPV recommenders”—those who did not consistently or strongly recommend the HPV vaccine—were also less likely to perceive their peers as thinking the HPV vaccine was important for adolescents or strongly recommending the vaccine (Hopfer et al, 2019 ).…”
Section: A Multilevel Framework For Factors Influencing Provider Reco...mentioning
confidence: 99%